Scars of war : migration, security and sustainable future - Stefanelli, Maria Anita; Skórzynska, Izabela (Research in political sociology, 2025)
This commemorative 30th-anniversary volume of Research in Political Sociology delves into the ramifications of warfare and conflict on migration, sustainable development, and security. What threat is posed by warfare and conflict to environmental integrity, security, and the prospects of a sustainable future? Echoing the sentiments expressed in pivotal UN resolutions and positions which emphasize the inherently destructive nature of warfare on sustainable development, the chapters focus on the importance of adhering to international legal frameworks for safeguarding the environment during armed conflicts. Recognizing the pervasive ramifications of warfare across diverse socio-cultural contexts, this volume convenes scholarly insights from three continents Europe, the Americas, and Asia to elucidate the far-reaching implications of conflict on environmental sustainability and harmonious cohabitation among nations. Beyond this, contributors underscore the indispensable role of women in environmental management and development and emphasize their full participation in developmental efforts even amidst wartime conditions as crucial for fostering international peace and security. Through a shared emphasis on the transformative power of education, this volume collectively underscores the urgent need to address the severe and enduring consequences of warfare on global ecosystems and collective well-being.